Single-cell elderly blood–CSF atlas implicates peripherally influenced immune dysregulation in normal pressure hydrocephalus - Phan Q. Duy; Emre Kiziltug; Ana B.W. Greenberg; Neel H. Mehta; Le T. Hao; Carla Fortes; Susan Mullany; Baojian Fan; Ani Manichaikul; Andrew F. Teich; Diane Chan; Seth L. Alper; et al. (Proceedings of the National Academy of Sciences, 2025)
We have generated a single-cell RNA sequencing atlas of peripheral blood and ventricular CSF in idiopathic normal pressure hydrocephalus (iNPH) patients totaling 140,207 single-cell transcriptomes. We found proinflammatory alterations in peripheral blood and CSF monocytes in iNPH patients with lower baseline cognitive function. We also identified CSF cell populations likely representing periventricular sloughing of degenerating neuroglial cells. Our findings suggest possible immune dysregulation in the blood and CSF of iNPH patients.